2011
DOI: 10.1093/qjmed/hcr133
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term outcome of patients with severe acute kidney injury requiring renal replacement therapy

Abstract: The short- and long-term survival outcome of severe AKI requiring RRT remains poor. Among those who survive, a significant number either continue to require RRT or have residual renal impairment necessitating ongoing follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…One-year mortality in our study was 38.8%, along the lines of previous findings [45,46,47]. Interestingly, the presence of DM or HTN did not influence 1-year mortality.…”
Section: Discussionsupporting
confidence: 91%
“…One-year mortality in our study was 38.8%, along the lines of previous findings [45,46,47]. Interestingly, the presence of DM or HTN did not influence 1-year mortality.…”
Section: Discussionsupporting
confidence: 91%
“…The HANDOUT 1-yearsurvival of 44.6% compares well to 37% reported by Ng et al, 24 in a study including patients with preexisting CKD. In contrast, Carl et al 25 reported only 24.6% 1-year survival in a septic study population with AKI.…”
Section: Discussion Survivalsupporting
confidence: 82%
“…Among the critically ill patients admitted to the intensive care unit (ICU), approximately 4–15% develop AKI that requires renal replacement therapy (RRT), and AKI is associated with a significant in-hospital mortality rate of 50–80% [4], [5]. To date, RRT remains a critical supportive measure for AKI [6].…”
Section: Introductionmentioning
confidence: 99%